Quaternary Sediments in Geosites: Evidence from the Western Caucasus - Dmitry A. Ruban (Heritage, 2023)
Some previous studies have already highlighted the importance of Quaternary sediments as geoheritage, although the related knowledge remains incomplete and geographically biased. Unique Quaternary features are often overlooked in areas famous for their pre-Quaternary geoheritage. Moreover, the already established high-value linked to pre-Quaternary phenomena require comprehensive descriptions; therefore, it is reasonable to analyze the related Quaternary features (even if these are only locally unique). For the purposes of the present study, three localities that form parts of larger geosites, and which represent Quaternary sediments of Mountainous Adygeya in the Western Caucasus, are characterized. They are assessed qualitatively, with a general description of sediments and attention paid to their origin, potential scientific importance, and accessibility. The Rufabgo Canyon hosts colluvial megaclast sediments. The Dakh–Sakhray Confluence exhibits typical alluvial sediment where detrital clasts are mixed with rather numerous Fe-rich concretions washed out from the parent rocks. The Stonesea Range exhibits mixed eluvial–deluvial sediment formed as a result of the karstification of carbonates and the erosion of overlaying red siliciclastics. All these sediments are of interest to scientists because they can be employed for promising research projects, revealing the peculiarities of the local patterns of Quaternary sedimentation. The localities under consideration are geoheritage points within the larger geosites and are perfectly accessible. Aside from their use by scientists, these localities can potentially be used by geosciences educators to train university students in sedimentology. In two cases, the sediments are also aesthetically important for attracting tourists. Generally, Quaternary sediments should be considered together with the other unique features represented in the geosites of Mountainous Adygeya.